ANALISIS SEMIOTIK POSTER RAMAH LINGKUNGAN DI KELURAHAN MINTARAGEN KOTA TEGAL - Yulia Prima Sari, Wahyu Asriyani dan (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Pancasakti Tegal, 2020)
This research was conducted to find out the description of the markers that were marked, and the meaning contained in the environmentally friendly poster in the Village of Mintaragen, Tegal City. This research writer uses descriptive method. The theory used in this study is the theory of markers and markers by Saussure, which is then used by Roland Barthes, and the division of other signs. Based on the results of the study, the markers on this eco-friendly poster consisted of all the text and images on the poster that were posted on the announcement wall in the Mintaragen Urban Village, Tegal. Whereas markers are formed from environmental posters created to influence poster readers to preserve the region's environment. The meaning of the denotation on the environmentally friendly poster is the same as the sign found on the poster. Meanwhile the connotation meanings on environmentally friendly posters are very diverse, so the determination of meaning or interpretation depends on the knowledge, experience, background, and even the emotions of the reader.